Potential Antioxidant Activity of Tropical Brown Macroalgae Turbinaria Ethanol Extract from Kabung Island West Kalimantan - Mega Sari Juane Sofiana; Apriansyah Apriansyah; Bambang Kurniadi; Warsidah Warsidah; Rita Kurnia Apindiati; Ikha Safitri; Syarif Irwan Nurdiansyah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Naturally, the human body has tolerance to free radical attacks. However, the natural antioxidant ability will decrease when exposure to free radicals from within and outside the body occurs intensively. Antioxidants play potential preventive role to protect the body from damage associated with oxidative stress by free radicals. One of the potential marine resources used as an antioxidant is macroalgae. Turbinaria is widely distributed in tropical waters of Indonesia, including West Kalimantan. This genus produces secondary metabolites with several biological activities. This genus abundantly grows in Kabung Island. However, it has not been used by the local community, even tends to be considered as a weed that disturbs others marine biota. This study aimed to evaluate the potential antioxidant activity of tropical brown macroalgae Turbinaria ethanol extract from Kabung Island, West Kalimantan. antioxidant activity was evaluated using the DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenger method with UV-vis spectrophotometer. The result showed that the ethanolic extract had a high of potential antioxidant activity which IC50 was 87.31 mg/L and it was classified into strong antioxidant potential.